Facile and scalable synthesis of low-cost FeS@C as long-cycle anodes for sodium-ion batteries. Issue 34 (30th July 2019) - Yang, Dan; Chen, Weihua; Zhang, Xixue; Mi, Liwei; Liu, Chuntai; Chen, Linjie; Guan, Xinxin; Cao, Yuliang; Shen, Changyu
Abstract : Sodium ion batteries attract extensive attention owning to their earth-abundant elements and potential of low cost. Low-cost FeS@C as anode was prepared from the practical perspective including the simple synthesis method and sufficient cycle stability (97.6%, 3000 cycles). Abstract : Sodium ion batteries have attracted extensive attention due to their earth-abundant elements and potential for low cost. Iron-based materials not only satisfy these demands but also have high theoretical capacities and are of great commercial value. It is, therefore, necessary to conquer the problems of iron sulfide, including the synthesis method and insufficient cycle stability, from a practical perspective; however, only a few studies have focused on these points. In this work, FeS nanocrystals embedded in a carbon network (FeS@C) were prepared by a homogeneous carbothermal reduction strategy. The advantages of this preparation method are as follows: (1) low-cost and abundant raw materials, (2) green synthesis method without releasing sulfide, (3) simple production processes, and (4) easy large-scale production. The as-synthesized FeS@C demonstrates a long cycle life (97.6%, 3000 cycles) with relatively high initial coulombic efficiency (ICE), high capacity, and excellent rate capacity. The application of FeS@C was further confirmed via a pouch full cell.